Validation of Rapid Interactive Screening Test for Autism in Toddlers Using Autism Diagnostic Observation Schedule™ Second Edition in Children at High-Risk for Autism Spectrum Disorder - Kong, Xue-Jun; Sherman, Hannah Tayla; Tian, Ruiyi; Koh, Madelyn; Liu, Siyu; Li, Alice Chukun; Stone, William S. (Frontiers in Psychiatry, 2021)
The Rapid Interactive screening Test for Autism in Toddlers (RITA-T) is a fast and inexpensive early screening measure for autism spectrum disorder (ASD) that was tested previously in children 18-36 months-old; the current validation study compared the RITA-T with the Autism Diagnostic Observation Schedule™ Second Edition (ADOS-2). The hypothesis is to validate the RITA-T with comparison to the ADOS-2. Thirty-five individuals (18-84 months-old) identified as at risk for ASD received the RITA-T and the ADOS-2 during a single visit. Participants were split into two age groups and both whole-group and sub-group data analysis were conducted. With all participants, RITA-T scores correlated significantly with ADOS-2 total scores (P < 0.001), social affect (SA) sub-scores (P < 0.001), and restrictive and repetitive behavior (RRB) sub-scores (P < 0.05). Similarly, ADOS-2 total and SA scores were significantly correlated in both age groups, while the RRB sub-score was only significant in females (P < 0.05). Lastly, correlations using subgroups based on ethnicity were only significant in the minority (“Other”) group for ADOS-2 total scores and in the Asian group for SA sub-scores (P < 0.05). Our receiver operating characteristic analysis showed that the optimal cut-off score of the RITA-T was consistently at 14, with a sensitivity of 81% and a specificity of 86% in the combined age group; The area under the curve was 0.84 (95%CI: 0.69-0.99) for ASD diagnosed by ADOS-2 and 0.89 (95%CI: 0.79-0.99) for ASD diagnosed by DSM-5. The RITA-T performed similarly to the ADOS-2 when both were administered in a single visit. Significant correlations between the measures helps validate RITA-T potential usefulness as a rapid early screening measure of ASD. The studies involving human participants were reviewed and approved by the Institutional Review Board (IRB) of Massachusetts General Hospital (MGH, 2017P0000857).